2002
DOI: 10.1042/bj20011438
|View full text |Cite
|
Sign up to set email alerts
|

Impaired noradrenaline-induced lipolysis in white fat of aP2-Ucp1 transgenic mice is associated with changes in G-protein levels

Abstract: In vitro experiments suggest that stimulation of lipolysis by catecholamines in adipocytes depends on the energy status of these cells. We tested whether mitochondrial uncoupling proteins (UCPs) that control the efficiency of ATP production could affect lipolysis and noradrenaline signalling in white fat in vivo. The lipolytic effect of noradrenaline was lowered by ectopic UCP1 in white adipocytes of aP2-Ucp1 transgenic mice, overexpressing the UCP1 gene from the aP2 gene promoter, reflecting the magnitude of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 69 publications
1
26
0
Order By: Relevance
“…These differences in GWAT and IWAT may explain why effects in Bhmt Ϫ/Ϫ IWAT are more pronounced. Other investigators also report metabolic differences between GWAT and IWAT (39).…”
Section: Discussionmentioning
confidence: 99%
“…These differences in GWAT and IWAT may explain why effects in Bhmt Ϫ/Ϫ IWAT are more pronounced. Other investigators also report metabolic differences between GWAT and IWAT (39).…”
Section: Discussionmentioning
confidence: 99%
“…33 All the effects of transgenic UCP1 on the biochemical properties of white fat in the aP2-Ucp1 mice seem to be in agreement with the activation of AMPK (see above). Indeed, it was observed that UCP1-induced decrease in the ATP/ADP ratio in the subcutaneous white fat of transgenic mice 25 was also associated with a reduced ATP/ AMP ratio, increased activity of AMPK, and enhanced oxidation of FA. 27 Less dramatic changes were also observed in the gonadal fat of these mice.…”
Section: Amp-activated Protein Kinasementioning
confidence: 99%
“…In parallel, UCP1 transgene caused a downregulation of hormone-sensitive lipase (HSL), lowered its activity, and altered the expression of G-proteins in adipocytes. 25 The LPL activity in gonadal fat was higher in the transgenic compared to control mice, especially when the animals were fed a high-fat diet. 21 In agreement, we found that plasma TG levels were significantly lower in transgenic mice.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…That mitochondrial uncoupling in WAT could reduce obesity was found in 1995 by Kopecky et al (1995) using aP2-Ucp1 transgenic mice and explored systematically later on (Kopecky et al 1996a, b;Stefl et al 1998;Baumruk et al 1999;Rossmeisl et al 2000Rossmeisl et al , 2002Rossmeisl et al , 2005Flachs et al 2002;Matejkova et al 2004). In these mice, the fatspecific aP2 promoter was used to drive expression of UCP1 from the whole genomic DNA sequence, resulting in enhanced expression of UCP1 in both WAT and BAT of mice with C57BL/6 J background.…”
Section: White Adipose Tissuementioning
confidence: 99%